The Seventh Evaluation Report on Community Development and Some Allied Fields Vol. I - Planning Commission (Planning Commission, 1960)
Background. The primary objective of the evaluation of the CD programme should be to present a coordinated view of all its aspects so that the reader can come to an overall judgement on its achievement. Such a study should, moreover, be, as far as possible, objective; the data on which it is based should be collected according to scientific principles and methods and the intrusion of subjective elements into the analysis and conclusions cut down to the minimum.
Government of India Programme Evaluation Organisation Planning Commission
Government of India Programme Evaluation Organisation Planning Commission